CDK4/6-dependent activation of DUB3 regulates cancer metastasis through SNAIL1 - Tongzheng Liu (Nature Portfolio, 2017)
Overexpression of SNAIL confers tumour cells with cancer stem-like characteristics associated with tumour progression. Here the authors show that inhibition of CDK4/6 blocks tumour metastasis in triple negative breast cancer by targeting DUB3 which in turns deubiquitinates and stabilises SNAIL1.